2019
DOI: 10.7126/cumudj.432692
|View full text |Cite
|
Sign up to set email alerts
|

Is Novamin Toothpaste Effective on Enamel Remineralization? An In-Vitro Study

Abstract: Objectives: New bio-active glass containing toothpaste (NovaMin) is one of the most effective cariostatic products when used as a daily application the aim of this in-vitro study is to evaluate the influence of NovaMin on enamel remineralization. Materials and Methods: Twenty-eight sound human enamel samples were randomly divided into four groups (A-D) each having seven samples as follows: A (Novamin), B (1450 ppm NaF and Novamin), C (CPP-ACP), D (1450ppm NaF). After inducing caries-like lesions, each group wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 33 publications
(30 reference statements)
1
11
0
Order By: Relevance
“…It leads to the formation of a carbonate‐enriched HCA layer, which is similar to tooth mineral in structure and chemical composition, leading to the remineralization of ICLs (Burwell et al, 2009 ). Research has shown that dentifrices containing Calcium sodium phosphosilicate (Novamin®) and fluoride are more effective than fluoride alone in enhancing remineralization and inhibiting demineralization of carious lesions (Abbasoglu et al, 2019 ; Manchery et al, 2019 ; Wang et al, 2016 ). However, these past studies tested the efficacy of dentifrices by analyzing the surface roughness and hardness of lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It leads to the formation of a carbonate‐enriched HCA layer, which is similar to tooth mineral in structure and chemical composition, leading to the remineralization of ICLs (Burwell et al, 2009 ). Research has shown that dentifrices containing Calcium sodium phosphosilicate (Novamin®) and fluoride are more effective than fluoride alone in enhancing remineralization and inhibiting demineralization of carious lesions (Abbasoglu et al, 2019 ; Manchery et al, 2019 ; Wang et al, 2016 ). However, these past studies tested the efficacy of dentifrices by analyzing the surface roughness and hardness of lesions.…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with our present study's results, where the MD percentage increase was 38.4% and 35.5%, respectively. In addition, Zerrin et al found a 20.6% increase in surface hardness of lesions treated with Sensodyne repair and protect® (Abbasoglu et al, 2019 ), while Rao et al and Lippert et al found a 25% and 54.8% increase in surface hardness of lesions treated with Clinpro tooth crème®, respectively (Lippert & Gill, 2019 ; Rao et al, 2017 ). As these other studies only investigated H on the surface of lesions, while this study investigated EM and H across the depth of ICLs, the results are not fully comparable, although they were similar.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] At this point, the concept of remineralization has come into the picture. 1,[3][4][5][6][7] The effectiveness of the method and the product used in protective programs should be strong as well as easy to apply and low in cost, not requiring a professional application, reaching everyone with the individual application. 3,26 When the studies evaluating the effectiveness of remineralization of nano-hydroxyapatite in primary teeth are examined; it was observed that only three of them used dentifrice.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] Fluoride (F), which forms a more resistant fluorapatite structure than hydroxyapatite against acid attacks, is the most widely used agent for remineralization. [3][4][5][6][7] It has been understood that the mechanism of remineralization with topical fluorides is limited to the increase in surface hardness and resistance to demineralization only as a result of chemical and physical modification of the existing apatite surface, rather than recovering the lost minerals to form a new apatitic layer. [6][7][8]10 Based on the knowledge that superficial remineralization has a limited impact on improving aesthetic and structural properties, it is accepted that the ideal remineralization system should provide mineral recovery on deeper surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation